Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-1998 - Planning Commission (Planning Commission, 1997)
The Union Territory of Pondicherry consists of four regions, namely, Pondicherry, Karaikal, Mahe and Yanam lying geographically isolated from one another. Pondicherry region which is on the east coast, about 162 kms. south of Madras is the largest of these and consists of 12 scattered areas interspersed with enclaves of South Arcot District of Tamil Nadu. Karaikal region is about 150 Kms. south of Pondicherry and it is surrounded by Thanjavur District of Tamil Nadu. Yanam region is located about 840 kms. northeast of Pondicherry near Kakinada in Andhra Pradesh. Mahe region lies almost parallel to Pondicherry 653 kms. away on the west coast near Tellicherry in Kerala.
Planning and Research Department Government of Pondicherry